COVID-19 and changes in dental practices in the Brazilian Public Health System: perception of the oral health team - Moimaz, Suzely Adas Saliba [UNESP]; Nascimento, Carolina Carvalho Menez Pinto [UNESP]; Saliba, Tânia Adas [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (FapUNIFESP (SciELO), 2023)
The aim of this study was to verify the perception of the oral health team regarding work safety and aspects related to changes in dental practices during the COVID-19 pandemic. A descriptive, exploratory, quantitative, and qualitative cross-sectional study was conducted using an electronic questionnaire sent via email to health professionals (n = 197) affiliated with the Brazilian Public Health System (SUS), from December 2020 to September 2021, in a municipality located in the northeast of the state of São Paulo, Brazil. The variables of interest were sociodemographic characteristics and those related to the professionals’ perception of oral health care during the pandemic and its impact on these workers’ occupational safety. Descriptive statistics were performed, and the absolute and relative frequencies of quantitative variables were calculated, whereas lexical analysis was performed for textual content using the descending hierarchical classification (CHD). Out of the total sample, elective and urgent/emergency care was provided by 58.95% (n = 56); physical barriers were absent between the teams in 54.74% (n = 52); minimally invasive techniques were applied in 71.58% (n = 68); personal protective equipment (PPE) was replaced in 81.05% (n = 77) between appointments; and occupational safety was reported by 49.47% (n = 47). Textual analysis showed a decrease in appointments and consultations, with a longer interval between appointments. The professionals noticed changes in dental practices during the pandemic, mainly regarding the use of PPE, the type of treatment performed, the number of treated patients, and the greater time interval between consultations. The physical infrastructure of health units and the availability of PPE to patients needed some adjustments. A significant number of workers felt safe in providing dental care during the pandemic.
Keywords: COVID-19; Dentists; Health Personnel; Practice Patterns